(untitled) (Research, Society and Development, 2021)
Peripheral odontogenic myxoma (POM) is a rare and extra-osseous variant of odontogenic myxoma (OM), classified as a relatively rare benign odontogenic tumor, yet presenting locally aggressive behavior. The objective this manuscript is to report a case of POM in a 75-year-old patient, located in the right maxilla, and in addition, to perform a literature review of the data in relation to clinical, radiographic aspects, hypothesis of diagnosis, and treatment. A male patient, 75 years old, clinical examination constact the presence of a nodule, with a smooth surface, on the right upper alveolar ridge, measuring 20 x 25 mm, with a color similar to the mucosa, a softened consistency, involving teeth 14 and 15, and with an undetermined time of evolution was observed. The diagnostic hypothesis was a peripheral ossifying fibroma and differential diagnosis of peripheral giant cell lesion. An excisional biopsy was performed together with extraction of the involved teeth. Histopathological examination and histochemical reaction was confirm the histopathological diagnosis of POM. The reported case is extremely rare due to the clinical presentation of the lesion, causing bone resorption with tooth mobility. In addition, the age range of involvement is very different from that presented in the literature, between the second and fourth decade of life. The final diagnosis was very important, as it is a lesion with a great potential for recurrence, long-term follow-up should be more careful, and in case of recurrence, a new intervention must be performed.